The Influence of Small and Medium Enterprises (SMEs) Listing on the Ghana Alternative Market (GAX): Prevailing Factors - Barbara Johnson; Richard Angelous Kotey (Academic Journal of Economic Studies, 2018)
Ghana Alternative Market was set up for SMEs and startups, who usually did not meet the requirements of the main stock exchange, to be listed and have access to equity financing. However, it has not been successful at getting SMEs listed, recording only 4 listings since its inception. This motivated the study to access factors that affect SMEs listing on the Ghana Alternative Market. Using a quantitative approach, we sampled 50 SMEs, 21 Brokers and 3 SMEs already listed on the GAX. We found that over half of the SMEs had some information about the GAX. However, their knowledge with regards to the benefits of listing on the GAX as well as what they require to list is very limited. Also, the findings revealed that SMEs had a difficulty accessing stock market operators as well as stock market information. LDMs showed commitment to the development of the GAX, however their efforts at getting SMEs on board has been passive. SMEs sampled also showed that they are willing to swap from alternative funding sources to the GAX when their concerns are addressed. They also stated that the relevant stakeholders should provide more information and education about the GAX in order to make it a viable option for them.
Keywords: D53; E44; G15; 330; Alternative Stock Market; Ghana Alternative Market (GAX); Determinants